Natural collagen bioscaffolds for skin tissue engineering strategies in burns: a critical review. Issue 9 (13th June 2021) - Sundar, Gayathri; Joseph, Josna; C, Prabhakumari; John, Annie; Abraham, Annie
Abstract: Global strategies on burn management have brought significant reduction in burn associated infections and morbidity. Yet, full regeneration of the damaged skin tissue is a formidable challenge despite improvements in health and safety standards. Nevertheless, it becomes an unmet clinical need of the hour to search for improved functional remedies. This critical review highlights the relevance of skin tissue engineering strategies for natural biomimetic burn scaffolds, their various sources and possible scaffolding technologies. Collagen biopolymer with its regenerative, biocompatible, nontoxic, cost effective, and local availability attributes to the biomaterial of choice for addressing skin burns. Graphical Abstract: